Karakteristik Penumpang Bus Transjakarta - Hutapea, Sabungan Halomoan (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
The transportation Juzs become problem for a decade in Jakarta as the capital city of Indonesia. Theshortage of tranportation fleet and traffic jam which is hapJXned in the morning and afternoon for allweek dm;s Juzs recome phenomenon. T7te rond length in Jnknrtn is nbout 7650 Ian, where the road areaonly 6,2% of Jaknrtn totnl mm T7ns rond is do111i11nted /7y r'rsonal tmnsportnticm about 93% while thepublic transportntion only 7%. 7hls public trnnsportntion senies for 56% of traveling in a elm;, while thepsonal transportation senJes for 44 % of psonal car, while 53 % motorci;cle. T7ierefor the govemor ofJakarta must issue the poliCI; to prm.Tide mass transportation fie.et such as Transjakarta Bus whid1 couldgiz:e transportation sennce faster, comfort, and reliable cost for Jakarta citizen. T71is mass transportationis designed to be able to earn; out 210.000 person from 7 million trmieller inn dmj in Jnknrta, and thisnew mode of trrznsportntion will re n cluzrncterishc symbol of fnknrtn.